Effect of cyclic meditation on anxiety and sleep quality in sailors on merchant ships—A quasi-experimental study - Paranthatta, Sukesh; George, Titty; Vinaya, H. M.; Swathi, P. S.; Pandey, Mangesh; Pradhan, Balaram; Babu, Natesh; Saoji, Apar Avinash (Frontiers in Public Health, 2024)
Background: Sailors undergo anxiety and sleep disturbances due to prolonged journeys and the nature of their work on ships. Earlier studies indicate Cyclic Meditation (CM) being beneficial for managing anxiety and improving sleep quality. Thus, the current study was designed to investigate the effect of CM on anxiety and sleep quality among sailors.Materials and Methods: Fifty sailors were assigned to experimental (n=25) and control (n=25) groups. The experimental group received 45 min of CM, 7 days a week for three weeks.Control group continued with their routine activities and were offered CM practice the following three weeks. Hamilton Anxiety Scale for anxiety (HAM-A) and the Pittsburg Sleep Quality Index (PSQI) for sleep along with blood pressure and pulse rate were taken at baseline and by the end of 3 weeks. Data were analyzed using Repeated Measures Analysis of Variance (RM ANOVA) for within and between group effects.Results: Significant differences were found between the groups following three weeks for all the variables. Experimental group demonstrated reduced anxiety (p<0.001) and improved sleep (p<0.001) along with improvements in blood pressure and pulse rate. The control group did not show any significant changes following three weeks.CM could be incorporated as a routine for sailors to manage their anxiety and improve sleep quality during the period on board ships.